Tamil Nadu Health: Review Of Primary Health Centres And Schemes - Priya Sinha; Prof. Vani Narula (International Journal of Advanced Science and Technology, 2020)
The Healthcare system in Tamil Nadu has improved over the years. Tamil Nadu is one of the best performing states on health parameters, even better than national average. Infant mortality rate (IMR) roughly presents the health scenario of the area. The IMR for India is 33 (infant deaths per 1000 live births) and Tamil Nadu has IMR of 16. Among the major states in India, the state of Tamil Nadu ranks second lowest in Infant Mortality Rate (16) and one of the lowest in neo natal mortality rate (11), and seventh highest in life expectancy at birth (71.7 years). The improvement is attributed to action oriented approach towards increasing and improving the number of rural health facilities especially primary health centers, family planning programs, immunization and maternity benefit schemes, school health programs and raising awareness on good health practices. The achievements of health performance have been attracting researchers to study its health system and interventions. The present article is the review of the journal article, health statistics, survey reports, both government publications and international online data sources. The article is on performance of rural healthcare delivery system in Tamil Nadu especially the role of Primary Health Centres, the first formal contact for medical facilities at rural level.